Educação e catástrofe: repensando a espiritualidade a partir de Viktor Frankl - Borin, Luiz Claudio (2017)
The article tries to analyze the theme of spirituality in the face of catastrophic events, investigating how education can contribute to the reconstruction of the ills caused by such episodes. In teacher education, it is important to take into account the consolidation of normativity and the expressiveness of meaning as a means of understanding how traumas and catastrophes have become part of our daily lives. They come to occupy an empty place of sense, because people are only sensitized by shocking images. The discussion revolves around the thinking of Viktor Frankl, Especially from some of his major works in which we can cite "The Ignored Presence of God", “In Search of Meaning”, “A Sense for Life”, “The Suffering of a Meaningless Life”, “The Will to Sense”, among others, predicting the contribution of spirituality to the discussion of the theme in the hermeneutic perspective. The dilemma lies between an education that remains in the model of reproduction or an education that awakens the students to visualize new horizons, allowing new knowledge to happen in school environments, among them the spirituality that helps in "knowing how to express" and "knowing how to prevent ", or knowing how to prioritize the meaning of the human in all actions. In this case, education can collaborate in the discussion about the relation of spirituality to disasters, providing an understanding of spiritual reality through hermeneutics and, thus, the possibilities of treating the theme so as not to separate subjects from events that condition them to act that way. In this perspective, education has its humanizing potential reinforced by weaving the crossroads between education and Logotherapy, discussing the theme in an emancipatory dimension. Thus, spirituality in education aims to dissipate the existential cold, to melt the icy winter of the heart of contemporary man in his personal and community relations. Spirituality broadens the discussion in the academic dimension, so that it can create devices that contribute to the integral formation of the human being. For a long time, education was marked by the stigma of instrumentalization, nevertheless, the research analyzes like the Course of Night Pedagogy of the Federal University of Santa Maria aims at a formation focused on humanization and issues related to spirituality. Religious education becomes an alternative to understand problems that stem from the modern paradigm, in this way, we can make some considerations about the discipline in an attempt to give a more formative character to education.